Individualised flow-controlled ventilation versus pressure-controlled ventilation in a porcine model of thoracic surgery requiring one-lung ventilation: A laboratory study. Issue 11 (21st November 2022) - Spraider, Patrick; Martini, Judith; Abram, Julia; Putzer, Gabriel; Ranalter, Manuela; Mathis, Simon; Hell, Tobias; Barnes, Tom; Enk, Dietmar
Abstract : BACKGROUND: Flow-controlled ventilation (FCV) enables precise determination of dynamic compliance due to a continuous flow coupled with direct tracheal pressure measurement. Thus, pressure settings can be adjusted accordingly in an individualised approach. OBJECTIVE: The aim of this study was to compare gas exchange of individualised FCV to pressure-controlled ventilation (PCV) in a porcine model of simulated thoracic surgery requiring one-lung ventilation (OLV). DESIGN: Controlled interventional trial conducted on 16 domestic pigs. SETTING: Animal operating facility at the Medical University of Innsbruck. INTERVENTIONS: Thoracic surgery was simulated with left-sided thoracotomy and subsequent collapse of the lung over a period of three hours. When using FCV, ventilation was performed with compliance-guided pressure settings. When using PCV, end-expiratory pressure was adapted to achieve best compliance with peak pressure adjusted to achieve a tidal volume of 6 ml kg −1 during OLV. MAIN OUTCOME MEASURES: Gas exchange was assessed by the Horowitz index (= P aO2 /FIO2 ) and CO2 removal by the P aCO2 value in relation to required respiratory minute volume. RESULTS: In the FCV group ( n  = 8) normocapnia could be maintained throughout the OLV trial despite a significantly lower respiratory minute volume compared to the PCV group ( n  = 8) (8.0 vs. 11.6, 95% confidence interval, CI -4.5 to -2.7 l min −1 ; P  < 0.001), whereas permissive hypercapnia had to be accepted in PCV ( P aCO2 5.68 vs. 6.89, 95% CI -1.7 to -0.7 kPa; P  < 0.001). The Horowitz index was comparable in both groups but calculated mechanical power was significantly lower in FCV (7.5 vs. 22.0, 95% CI -17.2 to -11.8 J min −1 ; P  < 0.001). CONCLUSIONS: In this porcine study FCV maintained normocapnia during OLV, whereas permissive hypercapnia had to be accepted in PCV despite a substantially higher minute volume. Reducing exposure of the lungs to mechanical power applied by the ventilator in FCV offers a possible advantage for this mode of ventilation in terms of lung protection.